The effects of pre-season neuromuscular training on balance and strength in u14 Canadian alpine ski-racers - Doyle-Baker, P.; Kashluba, K.; Clark, M.; Fung, T.; Emery, C. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
Alpine ski-racing is a complex, multifactorial sport in which performance is influenced by a combination of psychological decision making, physiological, and functional, parameters. Factors such as muscular strength, agility, balance, coordination, flexibility, and aerobic and anaerobic capacities play a crucial role in alpine ski-racers` performance (Anderson et al., 1988; Turnbull et al., 2009; Gorski et al., 2014; Raschner et al., 2017). Specifically, the close relationship between balance for both performance and injury prevention suggests that alpine ski training should be systematically tailored toward balance development throughout maturation (Raschner et al., 2017). Research has predominantly focused on physical conditioning, yet more recently towards neuromuscular training (NMT) warm-up programs in mature populations (14 years and older), which are designed to target potential deficits in neuromuscular abilities, such as postural stability, lower limb muscular strength and power (Abernethy & Bleakley, 2007; 2009; Emery et al., 2015; Faude et al., 2015). Currently there is limited research evaluating NMT in children, adolescents, and youth (Pomares- Noguera et al., 2018). Physical conditioning strategies that benefit the overall performance (Gorski et al., 2014) are needed in this younger ski population (Müller et al., 2017; Spörri et al., 2017). For the last four years, exploratory research within the Southern Alberta ski-club system has been on going (Christie et al., 2017; Doyle-Baker et al., 2017). The Balance and Strength Exercises for injury prevention program (BASE) focused on investigating the feasibility of injury surveillance as well as evaluating dryland training in under 14 (U14) alpine ski racers. This research informed the following aim to investigate whether a structured 8-week NMT warm-up program during pre-season conditioning would improve lower limb balance and muscular power compared to a standard pre-season program in alpine ski racers 10-13 years old (U14).